CATALYSTS FOR SELF-RELIANCE IN WHERE THE CRAWDADS SING BY DELIA OWENS - Desyara, R.A Trivani; Manugeren, M.; Pawiro, Muhammad Ali; Siwi, Purwanto (Universitas Islam Sumatera Utara, 2024)
This research aims to provide an in-depth analysis of self-reliance and its major causes, focusing on the concept proposed by Emerson and other related theories and concepts. The study employs a sociology of literature approach, which is well-suited to examine the social environment of the characters within the literary work. Additionally, the behaviorism perspective is utilized to analyze the behavioral phenomena that arise in relation to self-reliance. According to Savatagi, the causes of self-reliance include social, economic, political, and human agency factors, which set the boundaries for this analysis. Delia Owens' novel Where the Crawdads Sing serves as the primary source for this qualitative descriptive study, with additional books and related publications as secondary sources. The findings indicate that Kya's self-reliance is primarily driven by unsupportive social conditions, which prevent her from becoming dependent on others. Instead, these conditions foster a perception of self-reliance that helps Kya develop into a strong, independent individual who does not rely on external help.